62 Changes in Point of Maximal Curvature During Collagenase Clostridium Histolyticum Injections for Peyronie's Disease. Issue 1 (1st April 2022) - Price, T; Burgon, H; Green, B; Brearton, K; Savage, J; Ziegelmann, M; Kohler, T; Helo, S; Trost, L
ABSTRACT: Introduction: Collagenase Clostridium Histolyticum (CCH) is commonly injected at the point of maximal curvature (POMC) for Peyronie's Disease (PD). However, many providers only evaluate the POMC at baseline and do not reassess during CCH injections. As PD plaques often extend over an extended region, it is currently unknown how much the POMC may change throughout a course of CCH treatment. Objective: We sought to evaluate for changes in POMC between series among men undergoing CCH injections. Methods: A prospective database has been maintained of PD men undergoing CCH injections at two institutions. POMC assessments were obtained prior to each series of injections after pharmacologic erection and were measured from the coronal margin to POMC. An analysis was performed comparing changes in POMC throughout the CCH course, including associated baseline demographic and disease characteristics. Results: A total of 445 men (mean age 55.9, mean PD duration 30.6 months) underwent CCH injections from Jan 2014 through Feb 2021. The mean baseline composite curvature was 63.7° (SD 23.7), and the mean distance to curvature was 3.1 cm. Among men who completed 4 series of CCH injections, the mean improvement was 21° (SD 20.6) or 31.7% (SD 33%). In reviewing changes in POMC, the largest change observed at any point within the CCH series was a median 1 cm (IQR 0.5, 2 cm; range 0, 9.5 cm). Compared to baseline, 58% of men experienced a POMC change of 1 cm or greater, 25% 2 cm or greater, and 12% 3 cm or greater during the course of CCH treatment. Age, duration of PD, and baseline curvature were not associated with changes in POMC, although the POMC itself was associated with extent of changes, with proximal curves more likely to experience more notable changes compared to distal ones (p<0.0001). The total improvement in curve was also variably associated with change in POMC, with those experiencing greater improvements noted to have larger change in POMC (p<0.05 for changes in composite curvature and p=0.07 for percent change from baseline). These findings would suggest significant evolution of the POMC during a course of CCH, particularly among men with mid shaft or proximal curves and among those with greater curve improvements. Findings would support a role for repeat curvature assessments prior to each series of CCH injections. Conclusions: Based on data from a prospective, two-institution series of PD men undergoing CCH injections, the POMC changes by ≥1 cm in the majority of men. Given the small volume injected with each CCH series, the clinical relevance of these findings and their impact on injector protocols merit further investigation. Disclosure: No